Online Learning Supporting Tools: An Analysis the Impact of Supporting Tools During the Pandemic of Covid-19 on Student Achievement - Widya Karmila Sari Achmad; Hotimah; Dinda Cahyani Anas; Amir Pada; Muhammad Faisal (Universitas Pendidikan Ganesha, 2023)
The spread of the Covid-19 virus, which has taken place since 2019, has resulted in several activities that are usually carried out in person or face to face to go online. The transition from offline learning to online learning requires teachers or students to have supporting tools to connect. This study aimed to analyze online learning supporting tools and student achievement and determine the effect of online learning supporting tools on student achievement at SD Negeri 12 Malacca during the Covid-19 Pandemic. This study uses ex-post facto techniques and a quantitative approach. Participants in this trial were students of grades IV, V, and VI, totaling 30 students. Purposive sampling was used to collect samples for this study. The information collected is through surveys and documentation. Before the data analysis test, prerequisite analysis tests, normality, and linearity tests were first carried out. The results of the normality test show that the data is normally distributed. Then, the results of the linearity test show that there is a direct correlation between student achievement and online learning support tools. Based on the hypothesis test results, it was found that the online learning supporting tools variable significantly influenced the student achievement variable. It was concluded that online learning supporting tools could improve student achievement.